PREVALENCE OF MENTAL HEALTH PROBLEMS IN ACNE PATIENTS - KHAN, MOHAMMAD ZUBAIR; NAEEM, ABIDA; MUFTI, KHALID A (Journal of Ayub Medical College Abbottabad, 2001)
Background: Acne is the most common of all skin diseases, the condition affects young people at the time when they are undergoing maximum social and physical change and can produce significant psychological scarring. This study was done to determine the Mental Health problem in Patients suffering from acne and to determine significant difference of mental health problems in acne patients in comparison to seborrheic dermatitis patients as a control group. Methods: 50 subjects with acne and 50 with seborrheic skin problems (13-25 yrs age) were included in this study through Psychiatry OPD of Lady Reading Hospital. Peshawar. The period of study was from March 1998 to August 1998. The patients were assessed for psychiatric problems by using WHO Guide to mental health in primary care ICD 10-chapter V primary care. The statistical significance was determined by chi square. Results: The data shows that out of 50 acne patients 19 (38%) were suffering from Depression, with a female predominance. The control group (seborrheic) presented lower prevalence of Depression i.e. 57% in females. Similarly, Anxiety problem in particular social anxiety were overall more in acne group (34%) as compared to seborrhea group (10%). A statistically significant difference was observed between the two groups indicating that depression and social anxiety was more in the acne group. A consistent finding in the study over six months depicted the difference between gender i.e. more females presenting with depression. Total Depressed Patients were 19, while total with suicidal Thoughts were 4 (21%). Conclusion: The importance of this study is to highlight depression among such patients.